Supporting SDG 11 Through Green Stormwater Infrastructure: SWMM-Based Flood Mitigation in a Tropical Watershed - Anik Sarminingsih; Nurhaliza Prasetyani; Andito Dharma Atmaja; Adrian Hartanto; Budi Prasetyo Samadikun (Postgraduate, University of Mataram, 2026)
The study sub-watershed covers 3475 ha with a main river length of 9.03 km. Rapid land-use change—residential areas grew by 623.84 ha while rice paddies declined by 1390.40 ha between 2013 and 2023—has reduced infiltration areas, increased impervious cover, and intensified peak runoff. Existing drainage infrastructure is insufficient to convey the 2-year design discharge, resulting in recurrent downstream flooding. This study analyzes existing hydrological and hydraulic conditions and designs rainwater management solutions through Green Stormwater Infrastructure (GSI) for flood mitigation and groundwater conservation. Design rainfall was estimated using Log Pearson III frequency analysis, while runoff and hydraulic responses were simulated using EPA SWMM 5.2. Three GSI alternatives were evaluated: 3946 infiltration wells reduced peak flood discharge by 15.64%; 37 retention ponds reduced peak flood discharge by 47.48%; and a combined system of 3181 infiltration wells and 33 retention ponds achieved the highest reduction of 64.11%. Channel normalization of the critical river segment (2U–3U) is essential regardless of the GSI alternative selected. The combined alternative is recommended as it simultaneously addresses flood peaks and groundwater recharge